2009
DOI: 10.1186/1471-2393-9-22
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death and associated conditions (Codac) – a utilitarian approach to the classification of perinatal deaths

Abstract: A carefully classified dataset of perinatal mortality will retain the most significant information on the causes of death. Such information is needed for health care policy development, surveillance and international comparisons, clinical services and research. For comparability purposes, we propose a classification system that could serve all these needs, and be applicable in both developing and developed countries. It is developed to adhere to basic concepts of underlying cause in the International Classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
133
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(141 citation statements)
references
References 27 publications
(32 reference statements)
0
133
1
4
Order By: Relevance
“…Understanding pathways leading to early stillbirth and spontaneous preterm birth at early gestation is also important to pursue. Despite the call in the Lancet Stillbirths Series for a uniform approach to the definition and classification of stillbirths, 28 a systematic review of worldwide causes of stillbirth showed continued use of disparate approaches across HICs (appendix p 34), rendering interpretation between countries difficult. Irrespective of this challenge, placental pathologies were clearly important, accounting for about 40% of stillbirths in systems designed to capture these pathologies.…”
Section: Future Researchmentioning
confidence: 99%
“…Understanding pathways leading to early stillbirth and spontaneous preterm birth at early gestation is also important to pursue. Despite the call in the Lancet Stillbirths Series for a uniform approach to the definition and classification of stillbirths, 28 a systematic review of worldwide causes of stillbirth showed continued use of disparate approaches across HICs (appendix p 34), rendering interpretation between countries difficult. Irrespective of this challenge, placental pathologies were clearly important, accounting for about 40% of stillbirths in systems designed to capture these pathologies.…”
Section: Future Researchmentioning
confidence: 99%
“…By 28 weeks’ gestation approximately 1 in every 250 pregnancies will result in a stillbirth in high‐income countries, with rates in low‐ and middle‐income countries as high as 1 in 22. Stillbirth is the final common endpoint of several pathologies,2, 3 yet most are unexpected and many unexplained 4…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of cause-and timing-specific mortality includes assessing trends in causes of death and changes in classification of death; comparing death rates among fetal, neonatal, and postneonatal periods over time; and assessing changes in cause and timing within categories of infant maturity. Definitions selected for use in a classification system for infant deaths and reliability of data for classification may also affect proportionate mortality [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Cause and Timing Of Infant Death: Definition And Methodsmentioning
confidence: 99%
“…Investigation of cause-and timing-specific mortality includes assessing trends in causes of death and changes in classification of death; comparing death rates among fetal, neonatal, and postneonatal periods over time; and assessing changes in cause and timing within categories of infant maturity. Definitions selected for use in a classification system for infant deaths and reliability of data for classification may also affect proportionate mortality [13][14][15][16][17][18][19][20][21][22][23].While several systems of classification of perinatal death exist [23][24][25][26][27][28], no single system has been adopted as a standard. Standardized systems exist including the International Statistical Classification of Diseases (ICD; series 9 and 10) codes, however, these classification systems are often cumbersome and complex.…”
mentioning
confidence: 99%